STUDY OF ELECTRONIC WASTE INVENTORY SYSTEM (E-WASTE) FROM HOUSE HOLD IN PAMENGKANG VILLAGE - Wirani, Ayu Puspa; Octoberry Julyanto; Wiwik Eko Pertiwi; Ghina Rizqandi Q.A; Erwan Darmawan (UJoST- Universal Journal of Science and Technology, 2023)
E-waste is all objects included in a wide variety of electronic devices and their developments ranging from large household electronic equipment such as refrigerators, air conditioners, cell phones, stereo systems, and other consumptive electronic devices, to computers that are discarded by their owners. This study aims to determine the potential amount of used electronic goods (E-Waste), the amount of electronic waste generation, electronic waste management and the potential value of electronic waste recycling generated by the community which if not managed will cause a negative impact on the environment and public health of Pamengkang Village, Kramatwatu District. The type of research used is descriptive and qualitative research with research techniques using surveys. This research uses literature and field research such as interviews, observations and questionnaires. with a sample of 32 respondents, the sampling technique using quota sampling. research data processing was carried out using SPSS tools. Data were analyzed using univariate analysis. The results of the univariate analysis showed that the most electronic waste generated by the community was a TV as many as 7 (21.9%) and a fan as many as 7 (21.9%) and for the management of electronic waste the most done by respondents, namely electronic waste management by storing 23 (71.9%). As for the highest recycling value of electronic waste in Pamengkang Village, namely electronic materials at a price of Rp. 30,000, -.